Intrathecal morphine attenuates acute opioid tolerance secondary to remifentanil infusions during spinal surgery in adolescents - Tripi, Paul A (J Pain Res, 2015)
INTRODUCTION: The unique pharmacokinetic properties of remifentanil with a context-sensitive half-life unaffected by length of infusion contribute to its frequent use during anesthetic management during posterior spinal fusion in children and adolescents. However, its intraoperative administration can lead to increased postoperative analgesic requirements, which is postulated to be the result of acute opioid tolerance with enhancement of spinal N-methyl-D-aspartate receptor function. Although strategies to prevent or reduce tolerance have included the coadministration of longer acting opioids or ketamine, the majority of these studies have demonstrated little to no benefit. The current study retrospectively evaluates the efficacy of intrathecal morphine (ITM) in preventing hyperalgesia following a remifentanil infusion. METHODS: We retrospectively analyzed 54 patients undergoing posterior spinal fusion with segmental spinal instrumentation, to evaluate the effects of ITM on hyperalgesia from remifentanil. Patients were divided into two groups based on whether they did or did not receive remifentanil during the surgery: no remifentanil (control group) (n=27) and remifentanil (study group) (n=27). Data included demographics, remifentanil dose and duration, Wong–Baker visual analog scale postoperative pain scores, and postoperative intravenous morphine consumption in the first 48 postoperative hours. RESULTS: The demographics of the two study groups were similar. There were no differences in the Wong–Baker visual analog scale pain scores in the postanesthesia care unit and on postoperative days 1 and 3. Pain scores were higher in the remifentanil group on postoperative day 2 (2.9 vs 3.8). Postoperative morphine requirements were similar between the two groups (0.029 vs 0.017 mg/kg/48 h for the control group and the study group, respectively). CONCLUSION: In patients receiving preincisional ITM during spinal surgery, intraoperative remifentanil does not increase postoperative analgesic requirements.